Factores de riesgo físicos, químicos, biológicos y ergonómicos a los que están expuestos el personal auxiliar de enfermería en el Hospital Regional Manuel Ygnacio Montero-Iess de Loja - Sinche Vanegas, Daniela Abigail (2015)
The World Organization of the Health (WHO), pointed out that for the year 2012, the workpeople of the sector were representing health approximately thirty five (35) million persons on a global scale, what is equivalent to 12 per cent of the labor force, the workpeople of these institutions turn out to be exposed (they have an accident or fall ill) due to the deficient working conditions and aspects organizacionales, a big social injustice being demonstrated this way towards this labor sector. The work in the health services is a potential risk which causes find in the ambiences of the ignorance, lacking in training, excess of confidence in the technology, resistance to the fulfillment of safety norms / rules and procedures of work badly planned. The present investigation developed in Regional Hospital “Manuel Ygnacio Montero“-IESS of Loja, whose general target was to identify the factors of physical, chemical, biological andergonomic risks to which they were exposed the personnel to Help of Infirmary, the study was, descriptive and transverse type, in which 78 persons took part; for the information securing there was used a survey that contained a questionnaire previously structured. The obtained results point out that during the labor activity they are exposed / you to: physical risk the noise that affects 83,33 %, chemical risk the exhibition to the virkom in 83,33 %, the biological risks are related to the exhibition to blood in 88,46 % and ergonomic risks related to the standing position and to positions inclined in the achievement of the labor activities. Keywords: Nursing assistants, occupational risks, physical risk factors, chemical risk factors, biological risk factors, ergonomic risk factors